Equal pay for equal work in the third world - Lehman, Hugh (Journal of business ethics, 1985)
If the principle of equal pay for work of equal value is valid, then the practice of paying workers in third-world countries at a lower rate than workers doing the same jobs in industrialized nations is unjust. Recently Henry Shue argued that the principle is not valid. In this paper I criticize Shue's arguments and offer additional arguments in support of his conclusion.